Biocatalytic Synthesis of a Diketobornane as a Building Block for Bifunctional Camphor Derivatives. Issue 11 (18th September 2013) - Hofer, Michael; Strittmatter, Harald; Sieber, Volker
Abstract Camphor is a natural terpene readily available in huge amounts with the potential to replace existing chemical compounds derived from fossil resources. To create new industrial applications of camphor, it is necessary to introduce additional functional groups into its non‐reactive carbohydrate backbone. With the P450cam enzyme system of Pseudomonas putida, it is possible to selectively oxidize the non‐activated C5 position of camphor with air under mild conditions to produce 5‐exo‐hydroxycamphor. In this study, the dehydrogenase enzyme that catalyzes the further oxidation of 5‐exo‐hydroxycamphor to the diketone derivative (FdeH) has been cloned and analyzed. Together with the P450cam enzyme system, FdeH was used to realize a cell‐free enzymatic cascade reaction producing 2, 5‐diketobornane at the lab scale. We show that this process is highly efficient in terms of NADH cofactor usage and reaction yield. The enzymatically produced 2, 5‐diketobornane was converted further into corresponding biobased diamine and diol compounds. Our results show the advantage of combining enzymatic and chemical catalytic synthesis for the development of new routes to novel terpene‐based bicyclic bifunctional derivatives.